2019
DOI: 10.1371/journal.pone.0211781
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Q fever among high-risk occupations in the Ilam province, the west of Iran

Abstract: Background Q fever is a zoonotic disease of great public health importance in Iran. This disease is presented with high phase I antibody development in chronic and high phase II antibody in the acute form of illness. This study was conducted to evaluate the seroprevalence of Q fever among high-risk occupations in the Ilam province in Western Iran. Methods and findings In this cross-sectional study, 367 sera samples were collected from five groups comprised of animal hus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
2
10
1
1
Order By: Relevance
“…Further, they demonstrate high seroprevalence of endemic Q fever in the countryside and in Bedouin populations. Furthermore, higher prevalence has been detected among people who have close engagement with livestock due to their occupations, such as animal husbandry workers (45.13%) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, they demonstrate high seroprevalence of endemic Q fever in the countryside and in Bedouin populations. Furthermore, higher prevalence has been detected among people who have close engagement with livestock due to their occupations, such as animal husbandry workers (45.13%) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Park et al (2018) declared that the seroprevalence rate of anti-C. burnetii phase II IgG antibodies was higher 13.46% (7 out of 52) among dairy cattle farmers who had the habit of consumption of raw cow milk in Korea versus a seroprevalence rate of 10.88% (127 out of 1,167) among those who didn't ever consume raw cow milk. As well, Mostafavi et al (2019) showed that the Iranian humans who consumed unpasteurized milk and dairy products had a higher seroprevalence rate of anti-C. burnetii phase II IgG antibodies 37.43% (67 out of 179) in comparison with a seroprevalence rate of 28.18% (51 out of 181) among those who didn't. On the contrary, Wardrop et al (2016) found in their study on humans in Kenya that there was no evidence of a correlation between consumption of cattle milk and C. burnetii seropositivity among humans.…”
Section: Discussionmentioning
confidence: 95%
“…Avian influenza virus Moderate poultry exposure (301-900 poultry-years) 21 Professional classification as a poultry seller 22 ≥10 years of occupational exposure 23 Another stall nearby, number of cages (more than five) 24 Workplaces near locations where H5N2 outbreaks in poultry were reported 25 Wholesale/retail live poultry markets 26 Female gender 22 23 Male gender 27 28 Coxiella burnetii Contact with small ruminants (sheep and goats) 29 Cattle contact at own or other farm 30 Keeping sheep or goats, exposure to arthropod bites 31 ≥3 daily goat-related tasks (milking, feeding, supply and removal, general animal healthcare and birth assistance), other goat breeds next to white dairy goat 32 Milking cattle, general healthcare of cattle, birth assistance, contact with raw milk, contact with cattle manure, contact with dead-born animals 33 Presence of cat(s) in goat stable, distance residence to nearest stable ≤10 m, distance to nearest positive farm 0-<4 km 28 Passed through the stores 34 Full working week, worked in cattle sector in the past 30 Age >50 years), rural area of residence, having little or no formal education 31 Lived as child on a ruminant farm, no farm boots for staff 32 Male gender 34 No respiratory protection mask 35 Living in rural areas 36 Hepatitis E virus Abattoir work, sewage work 37 Occupational contact with animals (forestry/pig farm workers) 38 Slaughterers 39 Exposure to soil, contact with swine 40 Having professions with exposure to pigs for more than 16.5 years 41 Unorganised swine farming 37 Woodcutting 42 Raw seafood processing 43 Feeding of pigs 44 Previous mission abroad (military forces) 45 Consumption of pork-liver sausages 37 Residence area 40 Age≥50 years, age group 25-34 years, ascending age, ages 40-49, 50-59, ≥60 and over 40 years 38 44 46-48 ≥7 working years ...…”
Section: Pathogen Disease Factor Workplace Factor Worker Factormentioning
confidence: 99%